The Youth Psychopathic Traits Inventory: Measurement Invariance and Psychometric Properties among Portuguese Youths - Pechorro, Pedro (2016)
The aim of the present study was to examine the psychometric properties of the Youth Psychopathic Traits Inventory (YPI) among a mixed-gender sample of 782 Portuguese youth (M = 15.87 years; SD = 1.72), in a school context. Confirmatory factor analysis revealed the expected three-factor first-order structure. Cross-gender measurement invariance and cross-sample measurement invariance using a forensic sample of institutionalized males were also confirmed. The Portuguese version of the YPI demonstrated generally adequate psychometric properties of internal consistency, mean inter-item correlation, convergent validity, discriminant validity, and criterion-related validity of statistically significant associations with conduct disorder symptoms, alcohol abuse, drug use, and unprotected sex. In terms of known-groups validity, males scored higher than females, and males from the school sample scored lower than institutionalized males. The use of the YPI among the Portuguese male and female youth population is psychometrically justified, and it can be a useful measure to identify adolescents with high levels of psychopathic traits.